PENGARUH KARAKTERISTIK INDIVIDU DAN GAYA KEPEMIMPINAN TERHADAP KINERJA GURU SMA NEGERI 3 MUARA BUNGO - Syofiatul Hidayah (LPPM Universitas Muhammadiyah Muara Bungo, 2021)
As a teacher or teacher educator is one determining factor for the success of any educational effort. Teacher performance in planning and implementing learning is a major factor in achieving teaching goals. This type of research is descriptive quantitative research, namely research that aims to describe or describe the characteristics (characteristics) of a situation or research object. The nature of this research is explanatory research, which aims to explain the position of the variables under study and the relationship between one variable and another. The results of hypothesis testing using the t test indicate that the Individual Characteristics variable (X1), the t-count value is 2.176, while the t table is 2.028. tcount> ttable, this means that H0 is rejected and Ha is accepted. Thus, individual characteristics have a significant effect on teacher performance, while in the leadership style variable (X2), the tcount is 3,140, ​​while the ttable is 2,028. tcount> ttable, this means that H0 is rejected and Ha is accepted. Thus, the leadership style has a significant influence on teacher performance. The results of the F test show that the value of Fcount is 8.184, while Ftable is 1.753, where Fcount> Ftable. This shows that H0 is rejected and Ha is accepted, which means that the alternative hypothesis proposed is accepted by all independent variables, namely individual characteristics and leadership style together have a significant effect on teacher performance. Based on the results of this study it was found that individual characteristics and leadership styles both partially and simultaneously had an effect on the performance of teachers at SMA Negeri 3 Muara Bungo.